Structuring IT qualifications: lessons from the German case - Grollmann, Philipp [Verfasser]; Tutschner, Roland [Verfasser]; Wittig, Wolfgang [Verfasser] (My University, 2007)
"The purpose of this article is to provide research findings on learning and the structuring of qualifications in the IT-sector in Germany and relate this to the international discussion on the structuring of qualifications for the IT-industry. The article is based on desk research as regards the international discussion. The empirical findings stem from a standardised survey and case studies on learning in the IT sector within Germany and analysis of supplementary studies. Two general approaches can be distinguished: one based on coherent occupational profiles and one based on market-driven smaller unit certificates. The German system can be interpreted as a hybrid. It includes elements of both, thus allowing for a direct comparison of the two approaches. The empirical findings illustrate an acceptance problem. The study also suggests that work process-oriented learning is not always sufficient to generate the necessary competences required for new tasks, that profiles do not correspond to the more comprehensive profiles in small and medium-sized enterprises and that they do not match career aspirations of employees." (Autorenreferat, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; T 3 Forschungsmethoden; Informationstechnik; Informationstechnische Bildung; Lernen am Arbeitsplatz; Kompetenzerwerb; Berufsbeschreibung; Zertifizierung; Fallstudie; Empirische Untersuchung